2022
DOI: 10.1073/pnas.2208934119
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cGAS-STING signaling by PPARα in a mouse model of ischemia-induced retinopathy

Abstract: In ischemic retinopathy, overactivated retinal myeloid cells are a crucial driving force of pathological angiogenesis and inflammation. The cyclic GMP-AMP synthase (cGAS) and stimulator of interferon genes (STING) signaling are key regulators of inflammation. This study aims to investigate the association of cGAS-STING signaling with ischemic retinopathy and the regulation of its activation. We found that protein levels of cGAS and STING were markedly up-regulated in retinal myeloid cells isolated from mice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Furthermore, we found that STING was upregulated in microglia/macrophages infiltrating the photoreceptor after LD. Interestingly, during the preparation of the manuscript, Ma et al reported elevated cGAS and STING expression in retinal myeloid cells in oxygen-induced retinopathy (OIR), and knockout or inhibition of STING alleviated microglial activation in OIR [ 42 ]. Therefore, considering our scRNA-seq findings that cGAS-STING components are enriched in retinal microglia/macrophages, suppressing cGAS-STING in retinal microglia/macrophages cells may be beneficial in treating retinal degenerative diseases and retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that STING was upregulated in microglia/macrophages infiltrating the photoreceptor after LD. Interestingly, during the preparation of the manuscript, Ma et al reported elevated cGAS and STING expression in retinal myeloid cells in oxygen-induced retinopathy (OIR), and knockout or inhibition of STING alleviated microglial activation in OIR [ 42 ]. Therefore, considering our scRNA-seq findings that cGAS-STING components are enriched in retinal microglia/macrophages, suppressing cGAS-STING in retinal microglia/macrophages cells may be beneficial in treating retinal degenerative diseases and retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Although these immune responses are intended to be protective, the cytokines generated by immune cells reduce visual acuity by causing fibrosis and inflammation [ 37 ]. It has been documented that HSV-1 can induce cGAS-STING signaling, which is an important cytosolic DNA sensor mechanism in innate immunity and an immune inflammatory route, and the activated STING initiates a sequence of downstream pathway activation and events that transcriptionally up-regulate inflammatory cytokines and other factors, such as IL-6, TNF-α and RANTES [ 38 , 39 , 40 , 41 ]. The hyperproduction of pro-inflammatory cytokines can drive pathological inflammation and exacerbate HSK [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…After homogenizing the image scale, the boundaries of the CNVs were delineated using the free selection tool and displayed in square micrometers (μm 2 ) [ 27 , 28 ]. Delineation of neovascular and avascular areas in OIR mice were referred to previous studies [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%